EPEN-51. CHILDHOOD INTRACRANIAL EPENDYMOMA: A MULTI-CENTER RETROSPECTIVE ANALYSIS. (4th December 2020) - Pickle, Emily Owens; Aguilar-Bonilla, Ana; Khallouq, Bertha Ben; Stapleton, Stacie; Sandler, Eric; Langevin, Anne-Marie; Libes, Jamie; Hanif, Iftikhar; Smith, Amy
Abstract: Ependymoma is a heterogeneous disease which is resistant to improvement. Current challenges are the unreliability of histologic classification, the uncertain role of adjuvant chemotherapy, and a lack of clinical trials integrating molecular and clinical diagnostics into risk-guided therapy. Ependymoma can show surprising latency, reoccurring many years after the original diagnosis. In this study, we performed a retrospective analysis of ependymoma cases treated at six centers over a period of 12 years. A total of 73 cases were submitted from six sites; 68 cases were retained for review. Median age at diagnosis was 4.1 years and gender was reported as male (50%) and female (50%). Histologic grade was reported as Grade II (49%) and Grade III (50%)(not reported: 1). Anatomic location reported as supratentorial (27%) and infratentorial (73%). Metastatic disease was reported in 9% of patients. At diagnosis, gross total resection was achieved in 59% of cases. Twenty-eight percent of patients have died, 59% of patients are alive (with and without disease), and 13% of patients are lost to follow-up. Maximal safe surgical resection is currently the best predictor of long-term survival but was achieved in only 60% of cases. Biology-based therapy will be the next step towards improving the prognosis of pediatric ependymoma.